Genomic Avenue to Avian Colisepticemia - Sagi Huja (American Society for Microbiology, 2015)
ABSTRACT Here we present an extensive genomic and genetic analysis of Escherichia coli strains of serotype O78 that represent the major cause of avian colisepticemia, an invasive infection caused by avian pathogenic Escherichia coli (APEC) strains. It is associated with high mortality and morbidity, resulting in significant economic consequences for the poultry industry. To understand the genetic basis of the virulence of avian septicemic E. coli, we sequenced the entire genome of a clinical isolate of serotype O78—O78:H19 ST88 isolate 789 (O78-9)—and compared it with three publicly available APEC O78 sequences and one complete genome of APEC serotype O1 strain. Although there was a large variability in genome content between the APEC strains, several genes were conserved, which are potentially critical for colisepticemia. Some of these genes are present in multiple copies per genome or code for gene products with overlapping function, signifying their importance. A systematic deletion of each of these virulence-related genes identified three systems that are conserved in all septicemic strains examined and are critical for serum survival, a prerequisite for septicemia. These are the plasmid-encoded protein, the defective ETT2 (E. coli type 3 secretion system 2) type 3 secretion system ETT2sepsis, and iron uptake systems. Strain O78-9 is the only APEC O78 strain that also carried the regulon coding for yersiniabactin, the iron binding system of the Yersinia high-pathogenicity island. Interestingly, this system is the only one that cannot be complemented by other iron uptake systems under iron limitation and in serum. IMPORTANCE Avian colisepticemia is a severe systemic disease of birds causing high morbidity and mortality and resulting in severe economic losses. The bacteria associated with avian colisepticemia are highly antibiotic resistant, making antibiotic treatment ineffective, and there is no effective vaccine due to the multitude of serotypes involved. To understand the disease and work out strategies to combat it, we performed an extensive genomic and genetic analysis of Escherichia coli strains of serotype O78, the major cause of the disease. We identified several potential virulence factors, conserved in all the colisepticemic strains examined, and determined their contribution to growth in serum, an absolute requirement for septicemia. These findings raise the possibility that specific vaccines or drugs can be developed against these critical virulence factors to help combat this economically important disease.